From melting ice to green shipping: navigating emission reduction challenges in Arctic shipping in the context of climate change - Liu, Huirong; Mao, Zhengkai; Zhang, Zhijun (Frontiers in Environmental Science, 2024)
The effects of global climate change have accelerated the melting of glaciers and the decline of sea ice coverage in the Arctic. In tandem with advancements in icebreaker and other shipping technologies, the navigability of Arctic shipping routes has dramatically improved. Given the geographical advantages of the Arctic region in terms of shipping routes and resource potential, various countries have implemented initiatives to secure a foothold in the Arctic shipping industry.However, the current shipping industry has not yet achieved the ideal state of net-zero emissions, and the rapid increase in Arctic shipping has brought serious and even irreversible negative impacts on the Arctic environment. The study employs Document Analysis and Policy Analysis to conduct an in-depth examination of legal and policy documents related to Arctic shipping, especially those from the past five years, systematically outlining the relevant legal and policy frameworks as well as their historical context. At the same time, interdisciplinary research methods are utilized to comprehensively assess the new challenges. It is concluded that against the backdrop of the Arctic region's unique and fragile environment, the International Maritime Organization and the Arctic Council are introducing increasingly stringent regulations for Arctic shipping, posing a complex array of challenges for the industry. Not only must it navigate the mounting pressure of emission reduction policies and intensifying public scrutiny, but it must also overcome a multitude of complex technical and operational hurdles. Consequently, the joint efforts of the international community are essential to promote the sustainable development and emission reduction goals of the Arctic shipping industry.